Review of the grass feeding leafhopper genus Gurawa Distant (Hemiptera: Cicadellidae: Deltocephalinae) from the Indian subcontinent with description of two new species - Gnaneswaran, R.; Viraktamath, C.A. (Association for Advancement of Entomology, 2013)
ABSTRACT: Three species of Gurawa, G. intermediata Pruthi, G. minorcephala Pruthi and G. vexillum Distant are redescribed and illustrated. Two new species of Gurawa with constricted head in front of eyes, G. ceylonica sp. nov. (Sri Lanka: Peradeniya) and Gurawa constricta sp. nov. (INDIA: Karnataka) are described and illustrated. A key to known species of Gurawa from the subcontinent is also provided. ©Association for Advancement of Entomology
Keywords: Gurawa; New species; Chiasmini; India; Sri Lanka